Biological Control in Venezuela - Vasquez, Carlos; Ferrer, Francisco; Colmenarez, Yelitza C. [UNESP]; Morales Sanchez, Jose; VanLenteren, J. C.; Bueno, VHP; Luna, M. G.; Colmenarez, Y. C. (Cabi Publishing-c A B Int, 2020)
Venezuela has a long history in application of pest biological control. The first attempts were recorded at the end of the 19th century with the use of Scelio famelicus for control of the migratory locust Schistocerca paranensis and continued in the middle of the 20th with the introduction of Rodolia cardinalis to control the citrus scale Icerya purchasi, Aphelinus mali for control of Eriosoma lanigera and the Amazonian fly Lydella minense to control the sugarcane borer Diatraea saccharallis. Although chemical control has been widely used by Venezuelan farmers, biocontrol has been implemented in some crops such as sugarcane and maize partially due to the development of artificial diets that allowed the mass production of some parasitoids such as Trichogramma spp., Telenomus remus, Cotesia flavipes and the predators Chrysoperla carnea and Orius tristicolor. This review shows data on emblematic cases of the utilization of biocontrol in Venezuela and also the prospect of using other invertebrate organisms (arthropod, nematodes) as well as microorganisms in different crops. Finally, since Venezuela has a very rich biodiversity, it is presumed that a large number of entomopathogens, predators and parasitoids remain to be discovered and evaluated for potential use in biocontrol programmes, increasing the possibilities of the use of biocontrol agents in new crops, and a large range of studies to be done.